Study on abattoir and clinical investigations on small ruminant reproductive disorders in Jigjiga, Ethiopia - Yikeber Walle; Mullusew Gashaw (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
Across-sectional study was conducted from December, 2016 up to April, 2017 in and around Jigjiga town, Ethiopia to determine female small ruminant reproductive disorders on ewes 183 (56.8 %) and does 139 (43.2 %) at abattoir and clinic. Many factors contribute for low small ruminant productivity including; feed shortage, poor feed quality, ineffective husbandry, health constraints and poor services. Abattoir post-mortem examination revealed that 65 of the female small ruminants examined including 36.3% of ewes and 27.6% of doe's were pregnant. A total of 26 (13%) and 12 (9.8%) female small ruminant reproductive disorders were observed in the abattoir/ postmortem and clinical investigations, respectively. Abortion/terminated pregnancy was observed in 19.4 % of the pregnant females including 2 clinical and 11 post-mortem abattoir cases. Prevalence of abortion/terminated pregnancy was relatively higher (p> 0.050) in doe's, in younger (< 2 years) animals, and in middle gestation period. The reproductive disorders observed in non-pregnant females include clinical and post-mortem uterine infection 18 (7.1%); clinical retention of placenta 6 (2.4%) and post-mortem pyometra 1 (0.4%). Frequency of uterine infection and retained placental was similar in different species and age-groups. However, both conditions were higher in better body conditioned (p > 0.050) and recently parturient (p < 0.050) non-pregnant female small ruminants. A total of 40 specimens were taken in the clinical and abattoir investigations. This comprised of fetal fluid aspirates 16 (40 %), vaginal swabs 12 (30 %), endometrial swabs 10 (25 %) and aborted fetal skin swabs 2 (5 %). A total of 46 bacteria representing 8 different groups were isolated from the genital specimens. Short Gram Positive Bacilli (23.9%), Streptococcus species (19.6%) and S. aureus (17.4%) were the major genital bacteria isolates. Generally 20 (43.5%), 12 (26.1%) and 14 (30.4%) of the bacterial isolates were found from fetal fluid aspirate/skin swab, endometrial swabs and vaginal swabs, respectively. The majority of bacterial isolates (73.9%) came from healthy genital specimens whereas 17.4 % and 8.7 % were isolated from abortion and uterine infection cases. In conclusion, Abattoir investigation showed that ewes and does in the study area showed seasonal breeding tendency.